Targeting Fluorescence Imaging of RGD-Modified Indocyanine Green Micelles on Gastric Cancer - Shao, Jun; Zheng, Xiaoming; Feng, Longbao; Lan, Tianyun; Ding, Dongbing; Cai, Zikai; Zhu, Xudong; Liang, Rongpu; Wei, Bo (Frontiers in Bioengineering and Biotechnology, 2020)
Early diagnosis and complete resection of the tumor is an important way to improve the quality of patients with gastric cancer. In recent years, near-infrared (NIR) materials show great potential in fluorescence-based imaging of the tumors. In order to realize a satisfied intraoperative fluorescence tumor imaging, there are two pre-requirements. One is to obtain a stabile agent with a relatively longer circulation time. The second is to make it good biocompatible and specific targeting to the tumor. Here, we developed an RGD-modified Distearyl acylphosphatidyl ethanolamine-polyethylene glycol micelle (DSPE-PEG-RGD) to encapsulate indocyanine green (ICG) for targeting fluorescence imaging of gastric cancer, aimed at realizing tumor targeted accumulation and NIR imaging. 1H NMR spectroscopy confirmed its molecular structure. The characteristics and stability results indicated that the DSPE-PEG-RGD@ICG had a relatively uniform size of < 200 nm and longer-term fluorescence stability. RGD peptides had high affinity to integrin αvβ3 and the specific targeting effect on SGC7901 was assessed by confocal microscopy in vitro. In addition, the results of cytotoxicity and blood compatibility in vitro were consistent with acute toxicity test in vivo, which revealed good biocompatibility. The biodistribution and tumor targeting image of DSPE-PEG-RGD@ICG were observed by an imaging system in tumor-bearing mice. DSPE-PEG-RGD@ICG demonstrated an improved accumulation in tumors and longer circulation time when compared with free ICG or DSPE-PEG@ICG. In all, DSPE-PEG-RGD@ICG demonstrated ideal properties for tumor target imaging, thus, providing a promising way for the detection and accurate resection of gastric cancer.